Investigation on the reduction of the oxides of Pd and graphite in alkaline medium and the simultaneous evolution of oxygen reduction reaction and peroxide generation features. (10th February 2016) - Kar, Tathagata; Devivaraprasad, Ruttala; Bera, Bapi; Ramesh, Rahul; Neergat, Manoj
Graphical abstract: Highlights: Reduction of GO, PdO and parallel evolution of ORR is investigated in 0.1 M KOH. The results are compared with those of carbon, graphite, c-RGO and Pd. Peroxide generation and ORR activity increase with reduction of GO to e-RGO. Peroxide generation decreases and ORR activity increases with reduction of PdO. Carbon-based materials show peroxide yield of 40–75% as compared to ∼5% with Pd/C. Abstract: Palladium oxide (PdO) and graphene oxide (GO) are subjected to electrochemical cycling in oxygen-saturated 0.1 M KOH electrolyte in the potential range (−1.2–0.2 V vs. Ag/AgCl (saturated KCl)) relevant to oxygen reduction reaction (ORR). Parallel to ORR, GO and PdO get gradually reduced to graphene and Pd, respectively. With cycling, the half-wave potential of ORR shifts positively with both the oxides. The simultaneous evolution of the peroxide oxidation current on the Pt ring electrode is investigated. On PdO that reduces to Pd, ORR proceeds by the four-electron reduction to OH − and the peroxide oxidation current on the ring electrode decreases with cycling. On the other hand, on GO that reduces to graphene, the ORR proceeds primarily by the two-electron reduction of oxygen and the peroxide oxidation current on the ring electrode increases with cycling. The voltammetric features stabilize with the reduction of the oxides. The ORR and the peroxide oxidation current on the ring electrode with electrochemically reduced GO (e-RGO), chemically reduced GO (c-RGO), carbon-black, and graphite are comparable and they are different from those of the Pd-based precious metal catalyst. The evolution of ORR polarization curves and the peroxide oxidation current on the ring electrode are explained on the basis of the removal of adsorbed-oxygenated species, oxides and by the hydrogen under potential deposition (Hupd ) at lower potentials. The results are supported with Koutecky-Levich plots and the voltammograms.